Barriers to Cleft Lip and Palate Repair Around the World. Issue 7 (October 2016) - Massenburg, Benjamin B.; Jenny, Hillary E.; Saluja, Saurabh; Meara, John G.; Shrime, Mark G.; Alonso, Nivaldo
Abstract : Supplemental Digital Content is available in the text Abstract : Background: Cleft lip and/or palate (CLP) is estimated to occur in 1 out of every 700 births, but for many people residing in low- and middle-income countries this deformity may be repaired late in life or not at all. This study aims to analyze worldwide provider-perceived barriers to the surgical repair of CLP in low- and middle-income countries. Methods: From 2011 to 2014, Smile Train distributed a multiple-choice, voluntary survey to healthcare providers to identify areas of need in CLP care worldwide. Data on provider-reported barriers to care were aggregated by year, country, and larger world regions. Results: A total of 1997 surveys were completed by surgeons and healthcare providers (60.7% response rate). The most commonly reported barriers were "patient travel costs" (60.7%), "lack of patient awareness" (54.1%), and "lack of financial support" (52.8%). "Patient travel costs" was the most commonly reported barrier in sub-Saharan Africa, the Middle East and North Africa, and South and Southeast Asia. "Lack of financial support" was the most commonly reported barrier in the Americas, Eastern Europe, and East Asia. Conclusions: This is the largest intercontinental study on healthcare provider-identified barriers to care, representing the limitations experienced by healthcare professionals in providing corrective surgery for CLP around the world. Financial risk protection from hidden costs, such as patient travel costs, is essential. Community health workers and nurses are critical for communication and linking CLP care to the rest of the community. Recognition of these barriers can inform future policy decisions, targeted by region, for surgical systems delivering care for patients with CLP worldwide.